Proses Pengambilan Keputusan untuk Mengembangkan Mutu Madrasah - Anwar, Herson (Nadwa, 2014)
The main meaning of decision-making by the headmaster is an act issuing a decision that is both tactical and operational such as planning programs to be achieved, implementation strategies and problem-solving strategies, thro-ugh a decision based on the election results of several solution alternatives decided to achieve madrasah goals. The decision-making activities include problem identification, problem formulation, and alternative selection deci-sions based on calculations and the various impacts that may arise. In the stage of decision making implementation, the headmaster of the madrasah as a leader must make many routine decisions in order to control activities in accordance with the plans. While in control stage that includes monitoring, inspection, and assessment of the implementation results was performed to evaluate the implementation of the decisions.